2016
DOI: 10.1071/sb16005
|View full text |Cite
|
Sign up to set email alerts
|

Fossil leaves of Banksia, Banksieae and pretenders: resolving the fossil genus Banksieaephyllum

Abstract: The genus Banksieaephyllum, originally erected for cuticle-bearing fossil leaves of subtribe Banksiinae (Proteaceae subfamily Grevilleoideae, tribe Banksieae), is reassessed. Of the 18 described species, nine are accepted within Banksia, including Banksieaephyllum obovatum Cookson & Duigan, which is synonymised with B. laeve Cookson & Duigan on the basis of new cuticular preparations. Two other species are transferred to Banksieaefolia gen. nov., a genus erected for Banksieae of uncertain affinities, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 303 publications
(416 reference statements)
0
9
0
Order By: Relevance
“…8). The Lowana Road vegetation was distinct from that at Anglesea and Nerriga, with evidence for mangrove vegetation (Pole and Macphail 1996), diverse broadleaved angiosperms (Carpenter et al 2007;Carpenter et al 2012), diverse and common conifers (Bigwood and Hill 1985;Hill and Bigwood 1987;Hill 1990), and other gymnosperms (McLoughlin et al 2008). The vegetation may have been open canopied (Pole 1998).…”
Section: Discussionmentioning
confidence: 99%
“…8). The Lowana Road vegetation was distinct from that at Anglesea and Nerriga, with evidence for mangrove vegetation (Pole and Macphail 1996), diverse broadleaved angiosperms (Carpenter et al 2007;Carpenter et al 2012), diverse and common conifers (Bigwood and Hill 1985;Hill and Bigwood 1987;Hill 1990), and other gymnosperms (McLoughlin et al 2008). The vegetation may have been open canopied (Pole 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A regional Early Eocene flora was reported by Pole (2007) from dispersed cuticular remains. Mangrove species (e.g., the southernmost record of the mangrove palm genus Nypa; Pole and Macphail 1996) occur widely, and the (Rozefelds et al 2017), and probable rainforest angiosperms (Carpenter et al 2007;Conran et al 2009). Conifer fossils are diverse and common regionally, and they include representatives of the Araucariaceae (Bigwood and Hill 1985;Hill and Bigwood 1987;Hill 1990), Cupressaceae (Paull and Hill 2009), and Podocarpaceae (Wells and Hill 1989;Hill and Carpenter 1991).…”
Section: Lowana Roadmentioning
confidence: 99%
“…(Cookson and Duigan, 1950;Hill and Christophel, 1988). Some of these fossil taxa are clearly Proteaceae, but Carpenter et al (2016) have pointed out that some do not have epidermal details typical of Proteaceae, and are therefore unlikely to belong in the family. Of relevance here is a taxon that was first described as Banksia fastigata (Deane, 1925), which is smaller, but has a similar venation and margin as the Dinmore material.…”
Section: Multi-veined Conifermentioning
confidence: 99%
“…This was placed in Banksieaephyllum by Cookson and Duigan (1950), a genus accepted as Proteaceae by Hill and Christophel (1988). Carpenter et al (2016) reconsidered the material and concluded that the stomata "do not appear brachyparacytic," and both the form and location (restricted to epidermal cell junctions) Parataxon: DINM-JJI Figure 12 Reference specimen. Parataxon JBJ Figure 14 Reference specimen.…”
Section: Multi-veined Conifermentioning
confidence: 99%